Marketing elite authenticity: Tradition and terroir in artisanal food discourse. (April 2020) - Mapes, Gwynne
Highlights: Artisanal food practices can be enlisted in claims to superior taste and morality. Swiss German dialect contributes to the successful marketing of artisanal products. Mythologies of locality and authenticity circulate linguistically, visually, and materially. Elite Authenticity allows consumers to (re)frame high-status eating as natural and unpretentious. Abstract: Scholars have shown that 'slow' foods such as organic or artisan products are marketed primarily at the middle-class, allowing consumers to supposedly resist anonymous corporate culture and mass production, while at the same time performing cultural capital and "good taste" (cf. Bourdieu, 1984; Shugart, 2014). As a case in point, my paper examines a multimodal dataset of food texts (e.g. online resources, shop displays, and interviews) drawn from an artisanal cured meats producer in Switzerland who explicitly self-styles as the height of modern, cosmopolitan food practices and trends. This so-called 'progressive' discourse hinges on the iconization, romanticization and exploitation of agrarian life and peripheral vernaculars, in ways that strategically both claim and deny elitist distinction. I argue that this case study of Swiss artisanal food marketing therefore represents what I call "elite authenticity" (Mapes, 2018); as such, particular ways of eating (and particular eaters) are hailed as simultaneously fashionable and socially/politically virtuous (cf. Kenway and Lazarus, 2017), while covertly reinscribing privileged standards of good taste and class inequality.